Respuesta :

Answer:

y = [tex]3\sqrt{2} +4[/tex] ≈ 8.24

Step-by-step explanation:

Let's put some values of x and y into the equation to solve for a and b. We'll go with (60, 7) and (90, 4).

(60, 7): 7 = a * [tex]cos(60)[/tex] + b     ---- by basic trig, cos(60) = 1/2, so:

7 = 0.5a + b

(90, 4): 4 = a * cos(90) + b      ---- by basic trig, cos(90) = 0, so:

4 = b

We know b, so we can solve for a:

7 = 0.5a + 4

a = 6

Now, we have: y = 6cos(x) + 4

We can put 45 in for x and solve for y:

y = 6cos(45) + 4     ---- by basic trig, cos(45) = [tex]\sqrt{2} /2[/tex]

y = [tex]6*\frac{\sqrt{2} }{2} +4=3\sqrt{2} +4[/tex]

Thus, y = [tex]3\sqrt{2} +4[/tex] ≈ 8.24.

Hope this helps!

Answer:

4 + 3sqrt(2)

Step-by-step explanation:

y = acos(x) + b

4 = acos(90) + b

b = 4

10 = acos(0) + 4

a = 6

y = 6cos(x) + 4

At x = 45

y = 6cos(45) + 4

y = 3sqrt(2) + 4